IRAN AS AN EXPORTER OF NATURAL GAS TO THE SOUTH CAUCASIAN COUNTRIES - SAPRYKIN, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2005)
Many countries of the world have been engaged in serious rivalry for many years now over access to energy resources and the right to control their transportation routes. The energy industry has become a priority tool in world diplomacy for smoothing out international disputes and paving the way, if not to alliances, at least to reconciliation among neighboring countries. Of course, today no one knows who will be supplying the world with energy thirty years down the road and how this will be done, but experts assure us that the production and consumption of natural gas will increase at rapid rates, on an average of 2.4% a year (followed by oil at 1.6% and coal at 1.4%). And the price of blue fuel will also rise. What is more, there is no doubt that Iran, which currently occupies second place in the world (after Russia) in terms of supplies, will become one of the largest gas exporters to many Eurasian states. Despite resistance and competition from several other countries, this state is al-ready making plans to implement several gas-related projects on an extremely extensive territory in the next few years.Although Iran is beginning its gas expansion projects in the South Caucasian countries, Tehran intends to put significant pressure on Russia’s Gazprom in Europe as well, which could have a serious impact on the balance of power on this extremely solvent market and affect price formation.